APPLICATION OF THE CONCEPT OF "KAYZEN" IN SMALL BUSINESS AND ENTREPRENEURSHIP - Eshmurodova Shakhnoza , Shakhridinovna (THE INNOVATION ECONOMY, 2025)
This article analyzes the application of the "Kaizen" concept in small business and private entrepreneurship. The article examines in detail the basic principles of Kaisen and how it is used in small businesses in areas such as efficiency improvement, waste reduction, process optimization and Quality Management. In particular, the article analyzes strategies for successful implementation for small businesses through tools such as the 5S system, PDCA (Deming cycle), and Kaizen bidding system. Foreign experiments, including practices in Japan, the United States, and China, provide insight into the success of Cayzen's principles on a global scale. The article also includes views on the possibilities and difficulties of implementing this concept in Uzbekistan and other developing countries. The application of Kaisen's methodology in small business is recognized as an important tool for improving economic efficiency and sustainable development through innovative approaches.